Taking an Item‐Level Approach to Measuring Change With the Force and Motion Conceptual Evaluation: An Application of Item Response Theory. (5th November 2013) - Talbot, Robert M.
Abstract : In order to evaluate the effectiveness of curricular or instructional innovations, researchers often attempt to measure change in students' conceptual understanding of the target subject matter. The measurement of change is therefore a critical endeavor. Often, this is accomplished through pre–post testing using an assessment such as a concept inventory, and aggregate test scores are compared from pre to post‐test in order to characterize gains. These comparisons of raw or normalized scores are most often made under the assumptions of Classical Test Theory (CTT). This study argues that measuring change at the item level (rather than the person level) on the Force and Motion Conceptual Evaluation (FMCE) can provide a more detailed insight into the observed change in students' Newtonian thinking. Further, such an approach is more warranted under the assumptions of Item Response Theory (IRT). In comparing item‐level measures of change under CTT and IRT measurement models, it was found that the inferences drawn from each analysis are similar, but those derived from IRT modeling stand on a stronger foundation statistically. Second, the IRT approach leads to analyzing common item groupings which provide further information about change at the item and topic level.